The Effects of Subchronic Intake of Magnesium Hydrocarbonate-Rich Mineral Water on Cardiometabolic Markers and Electrolytes in Rats With Streptozotocin-Induced Diabetes - Djuric, Dragan M; Gatarić, Nina; Todorović, Dušan; Stanković, Sanja; Dragičević - Cvjetković, Dragana; Stojiljković, Miloš; Škrbić, Ranko; Vučković, Sonja (Scripta Medica, 2022)
Background/Aim: Hypomagnesaemia is one of the most detected electrolyte abnormalities in diabetics. Modulation of numerous cardiovascular pathophysiological processes is a potential goal for anti-diabetic therapy. Magnesium supplementation prevents subclinical tissue magnesium deficiency, thus delaying the onset of metabolic imbalance in diabetes, but long-term effects of magnesium supplementation in chronic diabetes and numerous pathophysiological processes remain unknown. Aim of this study was to determine the effects of subchronic intake of magnesium hydrocarbonate-rich mineral water on cardiometabolic markers and electrolytes in rats with streptozotocin-induced diabetes.Methods: A total of 28 Wistar, male rats, body weight 160 g at start, were divided into four groups of 7 each: two controls, group that drank tap water and received a single ip injection of saline (0.9 % NaCl) (TW-C), group that drank mineral water rich in magnesium hydrocarbonate and received a single ip injection of saline (0.9 % NaCl) (MW-C); and two experimental groups with streptozotocin-induced diabetes, group that drank tap water and received a single ip injection of streptozotocin (100 mg/kg) in saline (0.9 % NaCl, 1 mL) (TW-DM), group that drank mineral water rich in magnesium hydrocarbonate and received a single ip injection of streptozotocin (100 mg/kg) in saline (0.9 % NaCl, 1 mL) (MW-DM).Results: Regarding the biochemical parameters, a decrease was observed in the MW-C group for vitamin B12 and proteins, while triglycerides were higher compared to the TW-C group. By comparing the haemostatic biomarkers between TW-C and MW-C groups, a statistically significant decrease was found for fibrinogen, while the electrolyte analysis showed an increase in phosphates for the MW-C group. Biochemical value comparison between TW-DM and MW-DM groups showed that magnesium hydrocarbonate usage in diabetic rats did not significantly reduce glycaemia although the average glycaemic values were lower in the group treated with magnesium hydrocarbonate. Regarding the electrolyte values, a statistically significant decrease was observed for sodium, potassium and phosphate in the MW-DM group. The MW-DM group also showed a significant increase in iron value compared to TW-DM group.Conclusion: Subchronic intake of magnesium hydrocarbonate-rich mineral water, as a form of magnesium supplementation, did not cause a significant improvement in glycaemia or normalisation of diabetes-induced dyslipidaemia. This study showed the reduction of fibrinogen value, thus indicating the possibility of usage of this form of magnesium supplementation in different pro-thrombogenic conditions.
Keywords: Magnesium; Streptozotocin-induced diabetes; Cardiometabolic markers; Electrolytes; Rat